Impact of the 2019-2020 Australian Black Summer Wildfires on Photovoltaic Energy Production - Ford, Ethan; Hoex, Bram; Peters, Ian Marius (Conference Record of the IEEE Photovoltaic Specialists Conference, 2022)
Air pollution produced by the Australian Black Summer wildfires caused extreme haze events across New South Wales (NSW). We analyzed 30-minute resolution energy data from 160 residential PV systems in NSW from 6 November 2019 to 15 January 2020. A percentile data analysis technique was adapted to derive a mean reduction rate for PV energy generation with PM2.5. The mean power reduction rate for PV systems was approximately-12.5 % pm 2.2 % per 100 mu mathrmg/ mathrmm 3 of PM2.5 for airmass 1.0. The energy loss for residential PV systems was estimated as 39.8 pm 7.9 GWh, equating to a worst-case financial impact of 9.27 pm 1.85 million AUD. This work aims to help inform PV system planning and energy storage options of new PV systems; and raise awareness of the impact of wildfires and air pollution on solar PV.
CRIS-Team Scopus Importer:2023-03-07
Keywords: air quality; particulate matter; photovoltaic power generation; PM2.5; solar photovoltaic generation; wildfires